Impact and buckling of structures (AD-Vol.20 ;, 1990)
Impact deformation and failure analysis of laminated composite plates - Development of a water jet facility for reverse ballistics impact testing - Analytic interpretation of longo rod penetration experiments - Response of lamited kevler plates to projectile impact - Imperfection seensitivity and postbuckling behavior of laminated composite curved panels - Local buckling as failure initiation on pultruded composite curved panels - Local bucking as failure initiation on pultruded composite beams - Buckling analysis of pultruded composite columns - Thermal buckling of clamped symmetric laminated plates - Prediction of buckkling loads of stiffened composite panels - Effects of shear deformation and rotary inertia on the dynamic pulse buckling of a structure - General framework for analysis of buckling of viscoelastic structures - Random response of dynamic systems possessing principal and combination international resonances - Some remarks concerning the post-buckling behaviour of a compressible column.